Visual Online Control of Goal-Directed Aiming Movements in Children - Mackrous, Isabelle; Proteau, Luc (Frontiers in Psychology, 2016)
The present study investigated whether the initial impulse of goal-directed movements was visually monitored by 5- to 12-year-old children (n = 36) in a manner similar to adults (n = 12). The participants moved a cursor toward a fixed target. In some trials, the cursor was unpredictably translated by 20 mm following movement initiation. The results showed that even the youngest children visually monitor the initial impulse of goal-directed movements. This monitoring and the error correction process that it triggers seem automatic because it occurs even when the cursor jump is not consciously detected. Finally, it appears that this process does not fully mature before late childhood, which suggests that a putative dedicated channel for processing visual hand information develops during childhood.